Analisis Pengaruh Komunikasi Internal Terhadap Kinerja Pegawai di Dinas Kesehatan Pengendalian Penduduk dan Keluarga Berencana Kabupaten Kepulauan Anambas - Linda Ernawati; Asriwati Asriwati; Nuraini Nuraini (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The performance of health workers as a consequence of public demands for the need for excellent service or highquality service. It is expected to be able to show its professional contribution significantly in improving the quality of health services. The purpose of the study was to analyze the effect of internal communication on employee performance at the Anambas Islands Regency Population Control and Family Planning Health Office. The research design used the Analytical Survey method with a Cross Sectional approach. The population in this study were all employees as many as 98 people, all of whom were used as research samples with total sampling technique. Data analysis used univariate analysis, bivariate with chi-square test and multivariate with logistic regression. The results of logistic regression research show that there is an influence of leadership p = 0.001, motivation p = 0.000, trust p = 0.000, and appreciation p = 0.000. While the dominant factor that affects employee performance is appreciation p = 0.000 with Exp(B) 55.590. The conclusion of this study is that there is an influence of leadership, motivation, trust and appreciation. The dominant factor, namely appreciation, affects employee performance at the Anambas Islands Regency Population Control and Family Planning Health Office. It is recommended that the Anambas Islands Regency Population Control and Family Planning Health Office needs to provide direction to employees at work so that they have creativity at work so that employees continue to improve so that employee performance increases.